Comparison of recognition about denture adhesive between Japanese and Indonesian dentists: A pilot study - Shinsuke Sadamori; Taizo Hamada; Guang Hong; Nakai Nakai; Makoto Kawamura; Arifzan Razak (Dental Journal (Majalah Kedokteran Gigi), 2005)
The purpose of this study was to compare cross-national differences of the recognition of denture adhesive among dentists. The design of the research was cross-cultural differences. The research was done in Japan and Indonesia. One hundred and ten dentists from Japan and Indonesia were surveyed using a questionnaire regarding knowledge/comprehension of denture adhesive (in Japanese and Indonesian versions respectively). Logistic regression model (forward stepwise method) showed that it was possible to distinguish Japanese dentists from Indonesian peers with a probability of 96.0 per cent by using 4 items out of 16. For the question of "How many domestic products of denture adhesive (DA) do you know?" approximately a half of the Japanese dentists answered "less than 3", whereas 93 per cent of Indonesian subjects answered "nothing". It was concluded that there were much differences in dentists' understanding and experience of denture adhesive in the clinic, between Japan and Indonesia.